Hubungan Kualitas Tidur dengan Interpretasi Cold Pressor Test (CPT) pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh - Fadhila Dzakiyya; Cut Sidrah Nadira; Teuku Ilhami Surya Akbar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
High blood pressure cannot be judged as a mild disease. Hypertension often appears without symptoms so it is often called the "silent killer". Knowing the potential for hypertension early will reduce the risk of hypertension later in life. Cold Pressor Test (CPT) has the potential as an assessment in predicting the incidence of hypertension in the future. One of the factors that cause blood pressure is sleep quality. This study intends to examine the correlation of sleep quality with the interpretation of the Cold Pressor Test (CPT) on students of the Malikussaleh University Medical Study Program. This study used a cross-sectional quantitative research design with stratified random sampling technique, with a total of 195 respondents who met the requirements for inclusion and exclusion. The PSQI (Pittsburgh Sleep Quality Index) questionnaire was used to assess sleep quality and CPT was used as a predictor of hypertension risk. The results showed that the majority of respondents had good sleep quality (53.3%) and with the Cold Pressor Test (CPT) interpretation on normoreactor criteria (40.5%). Statistical tests using Rank Spearman showed a strong relationship between sleep quality and the interpretation value of the Cold Pressor Test (CPT) (r = + 0.691 and p-value = 0.000). The conclusion of this study is that the worse a person's sleep quality is, the worse the interpretation of the Cold Pressor Test will be.